Pengaruh Persepsi atas Model Pembelajaran Kooperatif dan Kemandirian Belajar Terhadap Pemahaman Konsep Matematika - Burhanudin; Suryana, Andri; Hasbullah (ALFARISI: Jurnal Pendidikan MIPA, 2026)
The purpose of this study was to determine: (1) The influence of perceptions on cooperative learning models and independent learning together on the understanding of mathematical concepts, (2) The influence of perceptions on cooperative learning models on the understanding of mathematical concepts, and (3) The influence of independent learning on the understanding of mathematical concepts. The research method used in this study is a quantitative method with a multiple linear regression survey approach. The sample in this study was 80 students using a proportion sampling technique. Furthermore, the data analysis technique used was a multiple linear regression analysis technique. The results of the study showed that: (1) There is a significant influence of perceptions on cooperative learning models and independent learning together on the understanding of mathematical concepts of students in State Senior High Schools in Central Jakarta. This is evidenced by a sig value of 0.00 < 0.05 and a calculated F value of 23.420. (2) There is a significant influence of perceptions on cooperative learning models on the understanding of mathematical concepts of students in State Senior High Schools in Central Jakarta. This is proven by the sig value of 0.00 < 0.05 and the calculated t value of 5.596 and (3) There is a significant influence of learning independence on the conceptual understanding of mathematics of high school students in Central Jakarta. This is proven by the sig value of 0.047 < 0.005 and the calculated t value of 2.021.
Keywords: Persepsi; model; pembelajaran; kooperatif; kemandirian; belajar; pemahaman; konsep; matematika